Innovative Strategies in Science Education: Implementing the POE Model to Enhance Elementary School Students' Science Process Skills - Reni Ramdayani; Kurnia Marifatul Latifah; Yurniwati Yurniwati; Taofik Taofik (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2023)
Effective science learning is designed and implemented for students who experience pressure in Science Process Skills (SPS). Therefore, this study aims to analyze the use of the POE (Predict-Observe-Explain) learning model to improve the Science Process Skills of Elementary School students. The research method used is Classroom Action Research (CAR) with the Kemmis & Taggart model consisting of planning, action, observation, and reflection. Data collection techniques were carried out through observation and tests, with the number of research subjects being 27 (15 women and 12 men). Then the data were analyzed descriptively. The analysis results in cycle I indicate an average value of 62%. In cycle II, there was an increase with an average value of 85%; in cycle III, there was a more significant increase with an average value of 96%. From these results, the POE model effectively improves students' science process skills, so this study contributes to developing innovative and effective science learning approaches. Thus, the results of this study have an important impact on the world of education, showing that using the POE model with realistic media can improve students' science process skills. This study also provides a basis for further research to delve deeper into the application and effectiveness of the POE model in other learning contexts and with different variations of realistic media.